Studying the effectiveness of marketing communications on digital platforms Case study of the 44 th House and Condo Show Expo By K2L ADVERTISING AGENCY COMPANY LIMITED - Kweankokkruad, Jirawadee; Satawetin, Patama (Siam Communication Review, 2025)
From a research study on the effectiveness of marketing communications with digital public relations strategies on digital platforms. Focusing on case studies at the 44th House and Condo Expo. K2L Advertising Agency Company Limited whose objective is1.To study marketing communications and formats of digital public relations strategies in organizing the 44th Home and Condo Expo and 2.) to study the effectiveness of digital marketing communication operations through digital public relations strategies that affect perception. Number of participants in advance The 44th House and Condo Fair using the research method is to useUsing digital marketing communication strategies and strategies, digital public relations strategies, digital digital through Facebook. From the study, it was found that digital public relations strategies for organizing exhibitions are effective and efficient in creating awareness and participation of the target group. It is considered a communication strategy that is consistent with behavioral trends. Consumers make the target group able to receive information. and various activities of the home fair and condos that are happening well Including encouraging the target group that has been set to participate in all activities, including online channels. Most visitors to the expo have a desire to buy a home and decide to reserve at the event immediately. The majority of visitors are Gen Y in the age group of 21-30 years, followed by those in the age group of 31-40 years. In addition, it was found that the Gen Z group born between 1997-2012 visited the fair more than before. which was promoted through various online channels such as Meta Ads, @Line, Google Ads, YouTube Ads, and TikTok Ads. These digital promotion strategies were used to attract the target audience and encourage them to join. work Which today's digital public relations strategies play an important role in creating cooperation and acceptance in various activities. Through the use of various communication strategies to effectively reach target groups.